Study on the Mechanism of Astragalus Polysaccharide in Treating Pulmonary Fibrosis Based on “Drug-Target-Pathway” Network - Bing, Pingping; Zhou, Wenhu; Tan, Songwen (Frontiers in Pharmacology, 2022)
Pulmonary fibrosis is a chronic, progressive and irreversible heterogeneous disease of pulmonary interstitial tissue. Its incidence is increasing year by year in the world, and it will be further increased due to the pandemic of COVID-19. However, at present, there is no safe and effective treatment for this disease, so it is very meaningful to find drugs with high efficiency and less adverse reactions. The natural astragalus polysaccharide has the pharmacological effect of anti-pulmonary fibrosis with little toxic and side effects. At present, the mechanism of anti-pulmonary fibrosis of astragalus polysaccharide is not clear. Based on the network pharmacology and molecular docking method, this study analyzes the mechanism of astragalus polysaccharidesAstragalus polysaccharides in treating pulmonary fibrosis, which provides a theoretical basis for its further clinical application. The active components of astragalus polysaccharidesAstragalus polysaccharides were screened out by Swisstarget database, and the related targets of pulmonary fibrosischronic heart failure were screened out by GeneCards database. Protein-protein interaction network analysis and molecular docking were carried out to verify the docking affinity of active ingredients. At present, through screening, we have obtained 92 potential targets of astragalus polysaccharidesAstragalus polysaccharides for treating pulmonary fibrosis, including 11 core targets. Astragalus polysaccharides has the characteristics of multi-targets and multi-pathways, and its mechanism of action may be through regulating the expression of VCAM1, RELA, CDK2, JUN, CDK1, HSP90AA1, NOS2, SOD1, CASP3, AHSA1, PTGER3 and other genes during the development of pulmonary fibrosis.